THE SYNONYMOUS CHARACTERS WITH THE ACTING FUNCTION OF HELPERS IN THE MACEDONIAN DRAMA FROM THE FIRST HALF OF THE 20TH CENTURY (PALIMPSEST / ПАЛИМПСЕСТ, 2024)
This paper titled "Synonymous characters with an actant function of assistants in the Macedonian drama of the first half of the 20th century" presents a semiological analysis of the synonymous characters in selected plays. It presents a semiological analysis of the synonymous characters with an actant function of assistants in the plays of Vojdan Chernodrinski: Macedonian bloody wedding, Masters, Spirit of Liberty; the drama in five acts by Nikola Kirov Majski, Ilinden; Vasil Iljoski's plays: Begalka, Chorbaji Teodos and Chest; Anton Panov's most famous play, Pechalbari; and Risto Krle's plays: Money is numbing, Antica and Million Martyrs. The analysis will be carried out using the techniques of character integration and the actant model by Algeridas Julien Greimas. Through the analysis of character synonymy, the paper ultimately identifies the synonymous characters with an actant function as assistants in some of the most prominent Macedonian dramas from the first half of the 20th century. Keywords: drama; character; signs; integration; synonyms.